1983
DOI: 10.1002/tera.1420270211
|View full text |Cite
|
Sign up to set email alerts
|

Some teratogenic properties of ethanol and acetaldehyde in C57BL/6J mice: Implications for the study of the fetal alcohol syndrome

Abstract: To investigate the teratogenic effect of acute alcohol exposure, pregnant C57BL/6J mice were exposed to 25% ethanol (either two doses of 2.9g/kg or one dose 5.8g/kg) during the organogenic period either by intraperitoneal injections or by intubation. The incidence of malformations varied according to (1) the stage of embryonic development at the time of exposure, (2) the route of administration of the alcohol, and (3) the amount of alcohol given and the time period over which it was administered. Oral doses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
112
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(129 citation statements)
references
References 11 publications
16
112
0
1
Order By: Relevance
“…We administered ethanol to pregnant mice on Day 7 of gestation. Some reports show the teratogenic effects of ethanol on mice fetuses, especially external anomalies, when administered to dams on the same period [25]. In this study, the size of the embryos at 24 hr after ethanol treatment was apparently smaller than those in control groups, it is considered that ethanol treatment induced growth inhibition in mice embryos.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…We administered ethanol to pregnant mice on Day 7 of gestation. Some reports show the teratogenic effects of ethanol on mice fetuses, especially external anomalies, when administered to dams on the same period [25]. In this study, the size of the embryos at 24 hr after ethanol treatment was apparently smaller than those in control groups, it is considered that ethanol treatment induced growth inhibition in mice embryos.…”
Section: Discussionsupporting
confidence: 41%
“…We administered ethanol to pregnant mice on Day 7 of gestation, since it is considered as organogenic period of mice [25]. In this study, significant increases of DNA damage were observed in brain, lung, and embryos of pregnant mice when administered 4 and 8 g/kg ethanol.…”
Section: Discussionmentioning
confidence: 90%
“…Webster et al [29] and Rasmussen & Christensen [30] also reported maxillary hypoplasia our study also reported the same. In our study maxillary and mandibular hypoplasia exhibited as either a flat mid face or a narrow snout that can be compared with the typical human FAS features i.e.…”
Section: Discussionsupporting
confidence: 84%
“…This notion has been supported by animal studies. Single intraperitoneal injections of ethanol given to pregnant C57BL͞6J mice between E7 and E11 resulted in craniofacial abnormalities, including exencephaly and hypoplasia of the midfacial region and anomalies of the DiGeorge sequence (68)(69)(70). The onset of expression of msx2 in mouse embryos has been reported to occur as early as E9 and is still expressed as late as E17 (26).…”
Section: Discussionmentioning
confidence: 99%